Awareness about the importance of zakat education among students of Academy of Contemporary Islamic Studies, UIiTM Puncak Alam / Hafizulizwan Mokhtar - Mokhtar, Hafizulizwan (2019)
Zakat is the payment made annually under Islamic law on certain kinds of property and used for charitable and religious purposes, one of the five pillars of Islam. The purpose of this study is to determine the awareness of Muamalat Students, Semester 5, Academy of Contemporary Islamic Studies, UiTM Puncak Alam about the concept of zakat. This study focuses only on the semester 5 students. The total number of students involved is 100 people (population). The method used is quantitative through the set of questionnaires using survey form among students of the semester 5. The results showed that the semester 5 students of this program had a mid-level understanding of the concept of the zakat especially about educational zakat based on the objectives of the study. In conclusion, it still needs a lot of effort to increase the awareness and knowledge about zakat concept, especially to the whole society.